Pengaruh Komunikasi dan Motivasi Kerja Aparatur terhadap Kualitas Pelayanan sertifikat Tanah - Sunarto Sunarto (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The subject matter of this research deals with the poor quality of land certification service and poor communication and working motivation of government employees at the Land Office ofSouth Jakarta Municipality. Another finding found was that communication would produce greater impacts with support of conducive transparency/openness through systematically institutionalized organizations so that availability, sufficiency and sustainability of communicators, messages, media and disturbance to process can be ensured and realized. Effects of Communication and Working Motivation of Government Employees on the Quality of Land Certification Service at the Land Office of South Jakarta Municipality. Working motivation will increase if it goes along with the application of the principles of integrated interest handling, that is if the organization’s interest is commensurate with the interest of management and personnel.